Perancangan Sistem Kontrol Heater Mesin Grinder Coffee Brewer Otomatis Menggunakan Metode Kontrol PI (Proportional Integral) - Khotib, Muhammad; Basri, Muhammad Hasan; Surya, Disma Adi; Iskawanto, Hilman Saraviyan (Universitas Trunojoyo Madura, 2021)
Coffee drink is one of the drinks favored by millennial people, where they relax and gather together. In an era of rapidly developing technology, many millennials are busy in the world of work who are required to do it quickly and on time, so they are very busy and most of them take short breaks to enjoy a cup of coffee. Therefore, to help facilitate the serving of coffee, an automatic coffee brewer heater control system was designed using PI control. Where the control is to control the hot temperature that will be made coffee using a heater. The results from testing the entire PTC sensor temperature set to 40 oC, the maximum temperature produced is 43 oC. And for the overall test of the heating temperature set at 35 oC, the time it takes to heat the water is 2.17 minutes, then after that the coffee will automatically come out of the heatear. For the temperature data carried out in this experiment, it was carried out from 30 oC to 90 oC with each experiment carried out by a heat transfer of 5 oC, to find out how long it took to heat the water in the heatear, so that it was suitable for coffee consumption by producing a glass of hot coffee that was ready to drink.